CLINICAL-PHARMACOLOGICAL APECTS OF THE USE OF DYDROGESTERONE IN PREGNANCY MAINTENANCE - E. V. Shikh (IRBIS LLC, 2016)
Dydrogesterone is a gestagen with proven pregnancy maintaining efficacy, which has been in common medical practice for more than 15 years in the Russian Federation and for more than 45 years outside of Russia. Dydrogesterone possesses the highest selectivity towards progesterone receptors among all progestins. The presence of an immunomodulating effect is a distinctive pharmacological feature ofdydrogesterone. This review touches upon the metabolism and biological effects ofdydrogesterone, as well as its use in complex pregnancy maintaining therapeutic regimens.